The identity dimension in Algerian historical narrative films – an analytical and critical view of Karim Belkacem's film - حليمة قمورة (International Journal of Social Communication, 2025)
The study examines the identity dimension in Algerian historical narrative films, focusing on the features of Algerian national identity, particularly its cultural aspect, through the film "Karim Belkacem" as an intentional sample due to its prominent characteristics related to language, religion, history, customs, traditions, values, and others. The study aims to highlight the issue of identity as one of the most important cultural issues raised within the framework of its interactions with the other, as well as to identify the contribution and role of historical narrative films in absorbing the issue of identity and its various dimensions and interactions. In this study, the historical method was employed to approach the facts and events of the film in relation to historical reality. The descriptive method was also adopted to approach the film's themes, analyzing and critiquing all the shots and film scenes that serve the subject of the study. The study reached several important results, most notably that the revolutionary narrative film "Karim Belkacem" interacted positively with the foundations of Algerian identity by focusing on several identity dimensions of Algerian society relating to land, history, language, and its concern with the value of land as one of the fundamental dimensions of Algerian society's identity.